2009
DOI: 10.1159/000229018
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Hemorrhage after Acute Ischemic Stroke and Its Risk Factors in Asians

Abstract: Background: The aim of this study was to examine the frequency and risk factors of gastrointestinal (GI) hemorrhage in acute ischemic stroke patients in Taiwan. Method: 920 patients admitted for acute ischemic stroke from January 2001 to October 2005 were included in the study. We reviewed the available medical records for any episode of GI hemorrhage, possible precipitating factors and administration of ulcer prophylaxis. Results: Seventy-two patients (7.8%) experienced GI hemorrhage; these patients were of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 52 publications
4
26
0
5
Order By: Relevance
“…3,9,11,12 Although ischemic stroke is included or involved in most studies, only 1 small-scale study suggested that the incidence of GI bleeding after ICH was about 30%, 3 which is similar to our present findings. However, because 63.4% of the patients in our study were prescribed SUP, the natural incidence of GI bleeding after ICH is still not clear.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3,9,11,12 Although ischemic stroke is included or involved in most studies, only 1 small-scale study suggested that the incidence of GI bleeding after ICH was about 30%, 3 which is similar to our present findings. However, because 63.4% of the patients in our study were prescribed SUP, the natural incidence of GI bleeding after ICH is still not clear.…”
Section: Discussionsupporting
confidence: 89%
“…13 Small-sample endoscopy data involving stroke patients showed that most patients who developed GI bleeding after stroke manifested esophageal ulcers, erosive gastritis or gastric ulcer. 11,12 In the present study, the exact cause of bleeding could not be ascertained in patients with GI bleeding, as their conditions were too serious to allow for endoscopy.…”
Section: Discussionmentioning
confidence: 80%
“…UTIs are associated with poorer neurological outcomes and longer hospital stays after stroke [44]. The prevalence of GI hemorrhage after acute stroke ranged from 0.5% to 30% [45], and was higher among ischemic stroke patients with CKD [46]. We also found that reduced eGFR was associated with poor functional outcomes upon discharge, which was similar to previous studies [12,24,30].…”
Section: Discussionsupporting
confidence: 87%
“…Gastrointestinal (GI) bleeding is a well-known complication that may occur during the acute phase of stroke [1,2,3,4,5,6] with an incidence of 0.1-8.0%, depending on the population studied. Previous studies have identified various factors associated with GI bleeding after acute ischemic stroke [1,3,4,6].…”
Section: Introductionmentioning
confidence: 99%